Pemaknaan Motif Hias Sarung Tenun Sutera Mandar dalam Pembinaan Karakter Siswa - Amri Amri (Ideguru: Jurnal Karya Ilmiah Guru, 2022)
This study aims to understand and explore the meaning of the decorative motif of the Mandar silk woven sarong as local wisdom in Polewali Mandar. The value of character education value is contained in the ornamental variety of Mandar silk woven sheaths. Internalization of the meaning of ornamental variety to the values of character education for learners in school. This study uses a qualitative descriptive research method through an anthropological approach. Data collection is done through library studies, interview, and direct observation. The object of his research is a variety of ornamental Mandar silk woven sheaths and students of SMA Negeri 1 Polewali. The results showed; 1. The ornamental variety of Mandar silk woven sheaths as the wisdom of local culture is in the form of a rectangular pattern. Having an essential meaning in its society includes relating to the symbol of the content of the universe and the noble values of human nature, namely honesty, justice and firmness of the establishment. 2. The value of character education values that exist in the ornamental variety of Mandar silk woven sheaths as the noble value of human nature can be transferred in the formation of student character including religious values, honesty, independence, hard work, creative, and cooperation. 3. Internalization of the meaning of ornamental varieties of silk weaving sarongs to the value of character values for learners can be realized by changes in attitudes, behavior, and appearance of students in interacting in school.